2011
DOI: 10.1128/aem.02385-10
|View full text |Cite
|
Sign up to set email alerts
|

The EIIABManPhosphotransferase System Permease Regulates Carbohydrate Catabolite Repression inStreptococcus gordonii

Abstract: Commensal oral streptococci play critical roles in oral biofilm formation and promote dental health by competing with, and antagonizing the growth of, pathogenic organisms, such as Streptococcus mutans. Efficient utilization of the spectrum of carbohydrates in the oral cavity by commensal streptococci is essential for their persistence, and yet very little is known about the regulation of carbohydrate catabolism by these organisms. Carbohydrate catabolite repression (CCR) in the abundant oral commensal Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 63 publications
2
49
1
Order By: Relevance
“…CcpA, the catabolite control protein, is believed to play a key role in CCR regulation in Gram-positive bacteria (8,15,17), whereas ManL, the glucose/mannose PTS permease, is also reported to be involved in CCR in S. mutans and S. gordonii (1,40,46,47). To further understand the regulatory mechanism of CCR in S. oligofermentans, we searched for ccpA homologs in the draft genome of S. oligofermentans using the S. cristatus ccpA gene (ZP_08059449.1) as a query and found a putative ccpA gene (ORF 247).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CcpA, the catabolite control protein, is believed to play a key role in CCR regulation in Gram-positive bacteria (8,15,17), whereas ManL, the glucose/mannose PTS permease, is also reported to be involved in CCR in S. mutans and S. gordonii (1,40,46,47). To further understand the regulatory mechanism of CCR in S. oligofermentans, we searched for ccpA homologs in the draft genome of S. oligofermentans using the S. cristatus ccpA gene (ZP_08059449.1) as a query and found a putative ccpA gene (ORF 247).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CcpA negatively regulates manL in other streptococci (40,46). We determined the manL gene expression in the wild-type strain of S. oligofermentans and the ccpA mutant using both qPCR and a luciferase reporter, which was constructed by fusion of the luc gene to the promoter of the manL gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose is one of the carbohydrates that strongly represses virulence gene expression in L. monocytogenes (17,26). In addition, components of the glucose-transporting PTS Glc in enterobacteriaceae (56) and the PTS Man in firmicutes (57) are involved in the general carbon catabolite repression mechanism. PTS Man components were therefore suggested to function as general virulence gene regulators in L. monocytogenes.…”
Section: Does Phosphorylation Of Eiibmentioning
confidence: 99%